2016
DOI: 10.1155/2016/4206908
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Degradation by Fibrinolytic Enzyme ofStenotrophomonassp. Originated from Indonesian Soybean-Based Fermented Food on Wistar Rats

Abstract: Objective. To evaluate thrombus degrading effect of a fibrinolytic enzyme from food origin Stenotrophomonas sp. of Indonesia. Methods. Prior to animal study, the enzyme safety was tested using cell culture. The effect on expression of tissue plasminogen activator was also analysed in the cell culture. For in vivo studies, 25 Wistar rats were used: normal control, negative control, treatment groups with crude and semipurified enzyme given orally at 25 mg/kg, and positive control group which received Lumbrokinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Results indicated that the Velefibrinase significantly ameliorated the length of the tail thrombus, and the therapeutic efficacy significantly surpassed that of an equal dose of urokinase. Moreover, the thrombolytic activity of Velefibrinase in vivo was found to be superior to that of Subtilisin QK [ 45 ], DEF [ 46 ], u-PA [ 47 ], and lumbrokinase [ 48 ], but inferior to that of streptokinase [ 43 ]. Therefore, this suggested that Velefibrinase is a safe thrombolytic or blood-thinning agent for clinical applications in patients with hyperfibrinogenemia and associated thrombolytic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the Velefibrinase significantly ameliorated the length of the tail thrombus, and the therapeutic efficacy significantly surpassed that of an equal dose of urokinase. Moreover, the thrombolytic activity of Velefibrinase in vivo was found to be superior to that of Subtilisin QK [ 45 ], DEF [ 46 ], u-PA [ 47 ], and lumbrokinase [ 48 ], but inferior to that of streptokinase [ 43 ]. Therefore, this suggested that Velefibrinase is a safe thrombolytic or blood-thinning agent for clinical applications in patients with hyperfibrinogenemia and associated thrombolytic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a fibrinolytic enzyme obtained from the Stenotrophomonas spp. and isolated from oncom (a soybeanbased fermented food) can dissolve blood clots in rats injected with kappa-carrageenan (Nailufar et al, 2016). The formation of an obstructive thrombus is closely related to extensive vascular disease.…”
Section: Improvement Of Cardiovascular Healthmentioning
confidence: 99%
“…Fermented soybeans have been consumed as traditional foods in many Asian countries, and indeed, they are sources of nattokinase and other fibrinolytic enzymes. These includes natto, a Japanese traditional fermented soybean obtained from fermentation with Bacillus subtilis G8 and Bacillus subtilis (Chang et al, 2012;Lucy et al, 2019), moromi, oncom and gambus (Indonesian traditional fermented soybean obtained from fermentation with Bacillus cereus, Bacillus subtilus, Bacillus pumilus, and Stenotrophomonas sp, respectively) (Afifah et al, 2014;Nailufar et al, 2016;Stephani et al, 2017;Syahbanu et al, 2020) as well as douchi and doufuru (Chinese traditional fermented soybean obtained from fermentation with Bacillus (Ok and Choi, 2005;Wang et al, 2006;Jo et al, 2011;Wei et al, 2011;Yuan et al, 2012;Chen et al, 2013;Heo et al, 2013;Park et al, 2013;Gad et al, 2014;Thokchom and Joshi, 2014;Bi et al, 2015;Huy et al, 2016;Liu et al, 2016;Nailufar et al, 2016;Hu et al, 2019;Ito, 2020;Syahbanu et al, 2020 (Shirasaka et al, 2012;Biji et al, 2016;Vijayaraghavan et al, 2016a;Vijayaraghavan et al, 2016b;Vijayaraghavan et al, 2019), seafood fermented with Bacillus sp, Bacillus. velezensis BS2, Bacillus pumilus BS15 and Bacillus coagulans (Anh et al, 2015;Prihanto and Firdaus, 2019;Yao et al, 2019;Kim et al, 2020) and liquors obtained from fermentation with Bacillus amyloliquefaciens, Bacillus licheniformis and Bacillus-Genus (Lapsongphon et al, 2013;Johnson e...…”
Section: Microorganisms As Sources Of Fibrinolytic Enzymesmentioning
confidence: 99%